Cyclophilin and Viruses: Cyclophilin as a Cofactor for Viral Infection and Possible Anti-Viral Target - Koichi Watashi; Kunitada Shimotohno Ph.D (AboutScience Srl, 2007)
Cyclophilin (CyP) is a peptidyl prolyl cis/trans isomerase, catalyzing the cis-trans isomerization of proline residues in proteins. CyP plays key roles in several different aspects of cellular physiology including the immune response, transcription, mitochondrial function, cell death, and chemotaxis. In addition to these cellular events, a number of reports demonstrated that CyP plays a critical role in the life cycle of viruses, especially human immunodeficiency virus (HIV) and hepatitis C virus (HCV). These two viruses are significant causes of morbidity and mortality worldwide, but current therapies are often insufficient. CyP may provide a novel therapeutic target for the management and/or cure of these diseases, in particular HCV.